1982
DOI: 10.1139/v82-398
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon ions in fuel-rich, CH4–C2H2–O2 flames as a probe for the initiation of soot: interpretation of the ion chemistry

Abstract: . Can. J. Chem. 60,2766Chem. 60, (1982.The ion chemistry is discussed for fuel-rich, nearly sooting, methane-oxygen flames at atmospheric pressure with added acetylene. Different types of ion-molecule reactions, both positive and negative, which can contribute through chemical ionization (CI) processes are summarized including their dependence on temperature, pressure, and equivalence ratio 4. Extensive data were presented previously involving ion concentration profiles measured with a mass spectrometer as af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 6 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…17- 20 The ultimate proof of this mechanism will require quantitative modeling. As the evidence continues to accumulate in support of the chemi-ionization, ion-molvcule mechanism of soot nucleation, many questions remain unanswered.…”
Section: Tp-443mentioning
confidence: 99%
“…17- 20 The ultimate proof of this mechanism will require quantitative modeling. As the evidence continues to accumulate in support of the chemi-ionization, ion-molvcule mechanism of soot nucleation, many questions remain unanswered.…”
Section: Tp-443mentioning
confidence: 99%
“…Small carbonaceous species, in both their neutral and ionic forms, are essential building blocks in several diverse chemical environments. Acetylene (C 2 H 2 ) and its cation C 2 H 2 + are ubiquitous in fuels, flames, planetary environments, and the interstellar medium (ISM). Much of the early understanding of C 2 H 2 + reactivity was developed from mass spectrometry studies of acetylene-rich flames, motivated by the hypothesis that ion–neutral reactions contribute to soot formation. , Far from these hot and dense environments, interest in C 2 H 2 + has more recently been focused on its role in colder and less dense regimes like planetary atmospheres and the ISM. Small cations of this type are thought to have a role in ion–neutral condensation reactions that may lead to the formation of larger, more complex organic species. ,, Understanding the reactivity of C 2 H 2 + in a controlled laboratory setting under low temperature and pressure conditions is crucial to understanding its reactivity in diverse chemical environments such as the ISM and planetary atmospheres.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear reactors, fusion, and magnetodynamic devices are examples of industrial appliances were such species are observed . The upper atmosphere, outer space, and flames are areas were charged clusters are being identified. The cluster structures in a small volume around the charged core often resemble the local order in condensed phases.…”
Section: Introductionmentioning
confidence: 99%